Predictors of HIV Risk Reduction in Adolescent Girls. Issue 3 (May 2019) - Long-Middleton, Ellen R.; Burke, Pamela J.; Rankin, Sally H.
Abstract: Purpose: The purpose of the study was to explore the associations among mastery, self-esteem, and HIV risk reduction behaviors in a culturally diverse group of adolescent girls. It is important to identify and assess psychological determinants of HIV risk reduction behaviors such as mastery and self-esteem so that healthcare interventions may be tailored to maximize an adolescent's preventive efforts. Study Design and Methods: Black, Latina, and White adolescent girls were recruited from an urban primary care setting in a tertiary care center. A descriptive, correlational design was used. Measures included the Pearlin Mastery Scale, Rosenberg Self-Esteem Scale, and the Adolescent Problem Severity Index. Data were collected through written surveys completed anonymously. Data were analyzed using multiple regression analysis. Results: There were 224 participants. Mastery and self-esteem, variables that commonly explain health-enhancing behaviors, were not associated with HIV risk reduction behaviors either in the entire sample or cultural subgroups. There was an inverse relationship between age and HIV risk reduction behaviors in all cultural groups. There were no significant differences in HIV risk reduction behaviors among the three cultural groups. Clinical Nursing Implications: Findings suggest HIV prevention efforts by nurses should be universal regardless of an adolescent girl's presumed level of mastery and self-esteem, and that these efforts need to intensify as they age. Abstract : HIV and AIDS remain significant public health problems. In this study, 224 adolescent girls were surveyed about their sexual activity and related HIV prevention behaviors. Mastery and self-esteem, variables that commonly explain health enhancing behaviors, were not associated with HIV risk reduction behaviors. Findings suggest HIV prevention efforts by nurses should be universal during care of adolescents and that these efforts need to intensify as adolescents age.